How Does Competition Affect Reputation Concerns? Theory and Evidence from Airbnb - Michelangelo Rossi (Center for Economic Studies and ifo Institute (CESifo), 2019)
I show how changes in competition affect the power of reputation to induce sellers to exert effort. The impact of competition on sellers' incentives is theoretically ambiguous. More com-petition disciplines sellers, but, at the same time, it erodes reputational premia. This paper identifies empirically whether one effect dominates the other using data from Airbnb. To guide the empirical analysis, I develop a model of reputation where the relative number of hosts and guests affects the value of building a reputation through effort. In this framework, more competition depresses hosts' profits and leads hosts to reduce effort. I test the model's predic-tion exploiting a change in regulation for Airbnb listings effective in San Francisco in 2017. I identify a negative causal effect of competition on effort. As the number of competitors sur-rounding each listing increases by 10 percent, ratings about hosts' effort decrease by more than one standard deviation. These findings suggest that more competition may erode incentives for high-quality services in markets where sellers' performances depend on reputation.
Keywords: D82; D83; L50; L81; 330; reputation; competition; digitization